German expressionism : Der Blaue Reiter and its legacies (Manchester University Press, 2020)
This book presents new research on the histories and legacies of the German Expressionist group Blaue Reiter, the founding force behind modernist abstraction. It offers a novel perspective on familiar aspects of Expressionism and abstraction, taking seriously the inheritance of modernism for the twenty-first century.